Sociology of Food - Cohen, Philip (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course uses food as an arena in which to develop our sociological imaginations, to understand how the issues and problems of daily life reflect larger social forces, and how our understanding and actions in turn shape the social world. Through our focus on food, we will treat the major questions facing sociology today, including inequalities and identities based on national, racial/ethnic, class and gender positions; work and family; the environment; globalization and cultural change. As an introductory seminar, we will encourage all kinds of question and discussion, and shape the course around our collective interests as we go.